Determination of total aflatoxin and aflatoxin B1 in groundnuts and cereal-based street vended foods sold in selected locations in Thika Town, Kenya: Total aflatoxin and aflatoxin B1 in street vended foods (Journal of Food and Dietetics Research, 2022)
Objective: Food contamination with mycotoxins such as aflatoxin in street vended foods is a public health concern in Kenya. The objective of this study was to determine the level of aflatoxins in street vended foods sold in six locations within Thika Town, Kenya.Methods: A total of 36 samples consisting of cereal and cereal based foods and groundnuts were randomly collected for analysis. Screening for aflatoxins was done using NEOGEN®'s Reveal® Q+ for Aflatoxin test kit while quantification of aflatoxin B1 and total aflatoxin was done through a competitive direct enzyme-linked immunosorbent assay (ELISA).Results: Total aflatoxin and aflatoxin B1 in street vended groundnuts averaged between 4.420 - 14.241 µg/kg and 3.431-11.289 µg/kg, respectively. Thika town center had significantly (p=0.0012) highest total aflatoxin and aflatoxin B1 level in groundnuts. On average 16.7% and 44.4% of groundnut samples had total aflatoxin and aflatoxin B1 levels above the regulatory limits of 10 μg/kg and 5 μg/kg established by the Kenya Bereau of Standards as limits for total aflatoxin and aflatoxin B1 in groundnuts, respectively. Compared to the 4 μg/kg and  2 μg/kg limit set by the European Union for total aflatoxin and aflatoxin B1, 72.2% and 100% of the samples were above these limits, respectively.Conclusion: This abundance of high levels of aflatoxins, especially aflatoxin B1, highlights the need for Kenya to take the necessary steps to effectively manage aflatoxins in ready to eat foods.
Keywords: Total aflatoxin; Aflatoxin B1; Enzyme-linked immunosorbent assay; street vended foods; food safety